Biomimetic mineralization of a hydroxyapatite crystal in the presence of a zwitterionic polymer. Issue 17 (6th April 2018) - Xu, Meng; Ji, Feng; Qin, Zhihui; Dong, Dianyu; Tian, Xinlu; Niu, Rui; Sun, Da; Yao, Fanglian; Li, Junjie
Abstract : The biomimetic mineralization of nano-hydroxyapatite using a zwitterionic polymer as a template to cognize the biomineralization of natural bone in vivo . Abstract : In this study, nano-hydroxyapatite crystals (nHAs) were prepared in the presence of zwitterionic poly(3-carboxy- N, N -dimethyl- N -(3′-acrylamidopropyl) propanaminium inner salt) (PCBAA) at different concentrations and pH microenvironments, denoted as Z-nHAs. The phase, morphology, size of apatite, and interactions between nHAs and PCBAA were systemically characterized via XRD, TEM, FTIR, and TGA. The results showed that Z-nHAs could be formed at all pH ranges in the presence of PCBAA in our experiment. It was different from the case of pure nHAs that could not be formed under an acidic microenvironment without PCBAA. In addition, a higher pH value was beneficial for the formation of nHAs with a smaller size. Z-nHAs exhibited a fiber-like structure at the initial 2 h and became rod-like in shape after 5 h, whereas pure nHAs prepared in water had an irregular flake-like structure. Moreover, 14–20% PCBAA could be incorporated into Z-nHAs via interactions between the quaternary ammonium group (–R3 N + ) and carboxyl group (–COO − ) in the PCBAA chain and Ca 2+ /PO4 3− of nHA. A possible mechanism for the formation of Z-nHAs in the presence of PCBAA was proposed based on the experimental results.